Assay for Quantitative Analysis of Losartan Potassium by using UV Spectroscopy (Global Journal of Medical Research, 2015)
Drug is a substance that brings about a change in the biological functions through its chemical actions. Drug losartan are the first marketed beta blockers of the angiotensin II-type (AT1) receptor. It is the prototypic ARB. Their pharmacologic effect are very similar to the ACE inhibitors, because they also produce the arteriolar and venous dilation and block aldosteron secretion, thus lowers the blood pressure, decreases the salt and water retention. Its chemical name is losartan potassium. It is indicated in mild to severe hypertension and contraindicated in pregnancy because it increases teratogenic risk and may leads to mal formation or death of fetus. It is light yellow solid and stable under recommended storage conditions, freely soluble in water and soluble in alcohol. Losartan inhibit the binding of angiotensin II to type 1 in tissue (kidney and adrenal gland) losartan and its active metabolite is more potent then losartan inhabitation causes vasodilation and decreases sodium and water retention. The aim of study is to determine the %age assay of losartan potassium of different brands.
Keywords: losartan potassium; anti-hypertensive; beta blockers